The comparison of peak flow rate with other spirometric measurements in cystic fibrosis patients - Göçmen, Ayhan (The Turkish Journal of Pediatrics, 1975)
This study was done to determine the role of the Wright peak flowmeter for evaluation of pulmonary functions in children with cystic fibrosis. Peak expiratory flow rate was measured with the use of a Wright peak flowmeter and one second forced expiratory volume, maximal mid-expiratory flow rate and maximal voluntary ventilation were measured with a spirometer in a total of 55 children, 25 of whom had cystic fibrosis disease, with the remainder being normal. Measurements were repeated after administration of bronchodilating drugs to the cystic fibrosis patients. All the values of the four measurements were decreased significantly in the cystic fibrosis patients. Positive and significant correlation co-efficients were obtained by comparing the peak flow rate with other spirometric measurements. It was concluded that peak expiratory flow rate is a feasible and useful measurement of pulmonary functions in cystic fibrosis patients. No changes were observed after administration of bronchodilating drugs to these patients.